EVALUATION OF THE INFLUENCE OF COMBINATIONS OF DRUGS FOR GENERAL ANESTHESIA ON CHANGE OF ACTIVITY OF STRESS-LIMITING AND STRESS-REALIZING LINKS ON THE CLINICAL MODEL OF ACUTE STRESS DAMAGE - Andrey Kolesnikov; Grigory Ignatenko; Georgiy Gorodnik; Aleksandr Grigorenko; Anna Kolesnikova; Igor Koktishev (Belgorod National Research University, 2017)
Introduction: When a person is in a state of anesthesia - sedation, the realization of the stress reaction is carried out through the mesocortical - limbic system, while performing intensive therapy outside sedation - through the amygdala and the hippocampus. In this regard, the response of the stress system under anesthesia and outside it will be different and, consequently, the evaluation of reactions during anesthesia is extremely interesting and necessary for targeted (individual) choice of combinations of drugs for anesthesia, depending on their effect on the links of the stress system. The more interesting is the response of the stress system in the conditions of the existing pathology, which in itself is accompanied by a stressful response. Objectives: Evaluation of the reaction of the stress system (with the identification of age-specific features), determining the response characteristics of the stress-realizing and stress-limiting links, determining the total response of the stress system, depending on the combination of drugs used for general anesthesia on the clinical model of general surgical acute stress (adults and children). Methods: Multicentre open clinical trial (2003-2015). This article presents the data of the group without the syndrome of intracranial hypertension (WSICH) - a general surgical group: 78 adults and 87 children. The group without SICH was interesting, as a group of "typical response" to stress in the form of trauma, emotional stress, pain factor. Two types of total intravenous anesthesia were used: standard (SA) - fentanyl, propofol and modified (MA) - fentanyl, propofol, ketamine, sodium oxybate. The markers of activity of the stress system (cortisol, corticotropic releasing factor (CTRF), β-endorphin, serotonin, histamine) were studied, the concentrations of interleukins in the blood serum (IL-4, IL-6, TNFa, IL-lß, IL-2). The study was conducted in the preoperative period and on the 5th-7th day after the operation. Statistical processing of the results was carried out. Results and discussion: The normal initial reaction of the stress-realizing-link (SR) of the stress system was determined (the normal stress-typical stress response in adults and children) on preoperative (psycho-emotional) and pain (traumatic) stress, which is expressed in: normal level of cortisol (adrenal level); normal level of CTRF (hypothalamic level); increased level of histamine; The normal level of IL1; normal level of IL6; increased IL2; decrease in the level of TNFα. The normal initial reaction of the stress-limiting-link (SL) of the stress system is determined which is expressed in: normal serotonin level in children and increase in 30% of adults (a typical pathophysiological reaction associated with age, which demonstrates the "vulnerability" of the SL link in adults); Reduction of β-endorphin level (a discussion on the need to enhance opioid exposure in order to prevent inadequate anesthesia); An increase in IL4 mean values. The typical reaction of the SR and SL - stress system links to the surgical intervention (surgical stress) using standard (group SA) and modified (group MA) variants of TIA was revealed. For the SR-link, increased cortisol levels, increased CTRF level, normalization of histamine level, normalization of IL1 indices, a decrease in IL6 level, an increased level of IL2, an increase in the level of TNFα. For the SL-link, serotonin level was decreased (decrease of the SL potential and the need for additional activation via NMDA receptors), increased β-endorphin level (adequacy of opioid stimulation of the SL-link), an increase in IL4 in 75% of adults and 80% of children Need for additional stimulation via GABA receptors). Conclusions: The "norm of pathology" (or "stress-norm") of the reaction of the SL-link (activation of stress-limitation), which can be estimated as normal when it is identical to the stimulation of the SR-link, for leveling the destabilizing influence of SR-stimulation, that is, Vegetative stabilization is achieved. In contrast to the SR-link, the possibility of combinations of drugs for general anesthesia to the activity of the SL-link receptors was revealed, the "point of application" for drugs was shown, with the prospect of developing techniques (new combinations) that could affect serotonin metabolism in the brain. It is possible to introduce a new concept - stress-limiting anesthesia, which is necessary, due to the received data that "depth of anesthesia" and "adequacy of anesthesia" are not identical concepts. Preparations for general anesthesia affect, first of all, the activity of the SL-link of the stress system and it is due to their combinations based on the initial activity of the stress system that it is possible to achieve adequate stress-limiting anesthesia.